2009
DOI: 10.1177/1933719109332828
|View full text |Cite
|
Sign up to set email alerts
|

Circulating and Uteroplacental Adipocytokine Concentrations in Preeclampsia

Abstract: Adiponectin increases in normal pregnancy but remains correlated with prepregnancy body mass index. Plasma leptin decreases in normal pregnancy. In preeclamptic women, the normal adipokine responses are perturbed and this could be of pathophysiological significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 31 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…Impaired placental development due to reduced trophoblast invasion is associated with PE and intra-uterine growth restriction. Altered plasma adiponectin concentrations have been described in women with PE (Takemura et al 2006a, Nien et al 2007, Fasshauer et al 2008, Herse et al 2009) reinforcing its possible implication on the control of trophoblast invasion.…”
Section: Discussionmentioning
confidence: 91%
“…Impaired placental development due to reduced trophoblast invasion is associated with PE and intra-uterine growth restriction. Altered plasma adiponectin concentrations have been described in women with PE (Takemura et al 2006a, Nien et al 2007, Fasshauer et al 2008, Herse et al 2009) reinforcing its possible implication on the control of trophoblast invasion.…”
Section: Discussionmentioning
confidence: 91%
“…Our preliminary study also indicated that plasma adiponectin in preeclamptic patients was significantly lower than in normal pregnant women. 2 Although the studies about serum adiponectin level in preeclampsia and normal pregnancy are not consistent, significant differences have been seen between normal pregnancies and preeclampsia cases. This finding suggested to us that adiponectin could regulate vascular endothelial cell function during normal pregnancy and might be involved in the pathogenesis of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…1 The prevention and management of preeclampsia are difficult, especially in severe cases, because the etiology and pathogenesis of preeclampsia are unclear. Recent studies indicate that the interaction of adiponectin and its receptors might have a considerable role in the pathogenesis of preeclampsia [2][3][4] because of their important physiological functions, including anti-inflammatory, anti-atherosclerotic, vascular endothelial cell protection and insulin-sensitizing effects. [5][6][7][8] Numerous single-nucleotide polymorphisms (SNPs) exist in the human adiponectin gene, located on chromosome 3q27.…”
Section: Introductionmentioning
confidence: 99%
“…3 Thus, a dysregulation in leptin levels may indicate or lead to maternal disease. For example, placental leptin expression 4, 5 and circulating leptin levels 4, 69 are exaggerated in preeclampsia, a systemic maternal disease characterized by the new onset of hypertension and proteinuria after 20 weeks of gestation. 10 As the only treatment for preeclampsia is delivery of the placenta, 10 which is often preterm, there is a need to identify biomarkers for early prediction or to identify women with severe subtypes who require different clinical management.…”
Section: Introductionmentioning
confidence: 99%